Safety, tolerability, pharmacokinetics, pharmacodynamics, bioavailability and food effect of single doses of soticlestat in healthy subjects. Issue 11 (5th May 2021) - Wang, Shining; Chen, Grace; Merlo Pich, Emilio; Affinito, John; Cwik, Michael; Faessel, Hélène
Abstract : Aims: Soticlestat is a first‐in‐class selective inhibitor of cholesterol 24‐hydroxylase, the enzyme that converts brain cholesterol to 24 S ‐hydroxycholesterol (24HC), a positive allosteric modulator of N ‐methyl‐D‐aspartate receptors. Soticlestat is under development as treatment for rare developmental and epileptic encephalopathies. Methods: In this first‐in‐human study, 48 healthy men and women received single ascending doses of soticlestat oral solution or placebo. Subsequently, nine healthy subjects received soticlestat tablets under fed and fasting conditions to assess the relative oral bioavailability and effects of food. Serial blood and urine samples were collected for pharmacokinetic and pharmacodynamic assessments. Results: Soticlestat appeared to be well tolerated up to a single dose of 1350 mg. Adverse events (AEs) were mild in intensity, and dose‐dependent increase in AE prevalence was not apparent. Soticlestat administered via oral solution was rapidly absorbed (median time to maximum plasma concentration [ C max ] 0.250–0.520 h). Mean C max and area under plasma concentration–time curve from zero to infinity increased by 183‐ and 581‐fold, respectively, over a 90‐fold dose increase. Mean terminal elimination half‐life was 0.820–7.16 hours across doses. Renal excretion was negligible. Administration of soticlestat tablets, and with food, lowered C max but did not affect overall exposure. Plasma 24HC concentrations generally decreased with increasing dose. Conclusions: Soticlestat appeared to be well tolerated after a single oral administration of up to 1350 mg and dose‐dependently reduced plasma 24HC concentrations. Systemic exposure increased in a greater than dose‐proportional manner over the dose range evaluated but was not affected by formulation or administration with food.